(untitled) (Bangladesh Journal of Scientific Research, 2014)
A long term incubation study was carried out to ascertain the effects of basic slag on acid sulfate soil. Four treatment levels of basic slag (0, 30, 40 and 50 t/ha) were selected to find out their response on pH, EC, as well as on various water soluble and exchangeable cations (Na, K, Ca, Mg and Fe) with incubation period. In most of the cases, the results showed significant effects of basic slag on pH and cations. The highest pH and EC were recorded with the largest doses of basic slag at the final stage of incubation period. In addition, this research did not find any negative impacts concerning basic slag on the supplied soil and suggested that basic slag could be used on agricultural land. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20225 Bangladesh J. Sci. Res. 26(1-2): 1-9, December-2013